Characteristics of vertical exchange process in the Pearl River estuary. Issue 3 (2nd July 2016) - Hong, Bo; Gong, Wenping; Peng, Shiqiu; Xie, Qiang; Wang, Dongxiao; Li, Haobo; Xu, Hongzhou
Abstract : Being an estuary with the occasional appearance of hypoxia, the Pearl River estuary was selected to investigate its vertical exchange process by a validated 3-D numerical model. The concept of vertical exchange time was used to quantify the vertical exchange process and was calculated by adding a conservative tracer to the hydrodynamic model. The results revealed vertical exchange time has significant seasonal variation modulated by seasonally changed external forcing, and has similar structure with spatial variation in salinity. During the wet season, remarkably long vertical exchange times (>50 days) occurred at the lower estuary under 10 m depth, which was coincident with the frequently reported hypoxic zone. The entire Pearl River estuary was occupied by water mass with a vertical exchange time of <5 days during the dry season, which indicated the estuary's health condition during this period. Further analyses revealed the seasonal trend of vertical exchange time was closely related with salinity stratification and river runoff in which the lowest vertical exchange times can be estimated by linear regressions in certain stages. Tide modulated these exchange times in different time scales. Spring tide better mixed the water column and thus facilitated the vertical exchange process compared with neap tide. As a result, minimum vertical exchange time during spring tide was about 10 days shorter than that during neap tide. Flood-ebb tide also modulated vertical exchange time in the Pearl River estuary. Vertical exchange time varies with the tide and reached minimum and maximum values during valley and high tides, respectively.